A Novel Tris(2-aminoethyl)amine Based Tripodal Ligand: Synthesis and Solution Coordination Studies with Trivalent Iron and Chromium. (23rd November 2016) - Baral, Minati; Gupta, Amit; Akbar, Rifat; Kanungo, Bikram K.
Abstract : A novel tris(2-aminoethyl)amine (TREN) based tripodal ligand TRENOL (L) has been synthesized and characterized by elemental analysis and UV-VIS, IR, 1 H, and 13 C NMR spectroscopic methods. The coordination behaviour of the ligand with H + and trivalent metal ions, Fe(III) and Cr(III), was investigated in aqueous medium at 0.1 M KCl at25 ± 1 °C by potentiometric and spectrophotometric studies. Tripodal ligand showed seven protonation constants in the adopted pH range 2–11 and its electronic spectra exhibited three bands at 216, 323, and 423 nm. Ligand formed various metal complex species of the type MLH5, MLH4, MLH3, MLH, and ML with trivalent metal ions. The determined values of the formation constants (for ML species) of the ligand with Fe(III) and Cr(III) were 24.19 and 18.64, respectively. Molecular modeling studies revealed that the metal complexes formed distorted octahedral geometry. Besides, ligand showed fluorescence at 496 nm when excited at 289 nm. The fluorescence behaviour of the ligand in the presence of Fe(III) ions showed noticeable quenching in comparison to the other metal ions at physiological pH (7.4). So, as per the outcomes of the present study, TRENOL has the potential to be used as the iron detector in environmental, agricultural, and medical fields.